Corporate Governance and Firm Size Fail to Influence Tax Avoidance in Indonesia - Nugroho, Dimas; Ernandi, Herman (Indonesian Journal of Law and Economics Review, 2024)
This study examines the influence of corporate governance and firm size on tax avoidance among manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2019. Using a sample of 10 companies selected through purposive sampling, the research employed multiple linear regression analysis. The findings reveal that neither corporate governance nor firm size significantly impact tax avoidance, with significance levels of 0.669 and 0.069, respectively. These results suggest that these factors do not play a crucial role in tax avoidance strategies in the examined companies, providing insights for policymakers and stakeholders in understanding tax planning behaviors. Highlights: 1. No significant impact of corporate governance on tax avoidance.2. Firm size non-influential on tax avoidance strategies.3. Limited role of these factors in Indonesian manufacturing firms. Keywords: tax avoidance, corporate governance, firm size, multiple linear regression, Indonesia Stock Exchange